Leistungsfähige Verbindungen des Ingenieurholzbaus - Einsatzmöglichkeiten für Nadel- und Laubholz - Enders-Comberg, Markus (Karlsruher Berichte zum Ingenieurholzbau / Karlsruher Institut für Technologie, Holzbau und Baukonstruktionen, 2015)
This book is about the invention of mechanical connections and contact joints to support the utilization of beech wood for structural applications. Further the influence of fastener holes in the tension and compression area of timber and glulam members on the load‐carrying capacity under load parallel to the grain was studied.